Remembering survival : inside a Nazi slave-labor camp - Browning, Christopher R. 1944- (W. W. Norton & Company, 2010)
pt. 1. The Jews of Wierzbnik -- The prewar Jewish community of Wierzbnik-Starachowice -- The outbreak of war -- The early months of German occupation -- The Judenrat -- The German occupiers in Wierzbnik-Starachowice -- Coping with adversity in Wierzbnik, 1940-1942 -- pt. 2. The destruction of the Wierzbnik ghetto -- Wierzbnik on the eve of destruction -- The Aktion, October 27, 1942 -- Into the camps -- pt. 3. Terror and typhus : fall 1942-spring 1943 -- Personalities and structures -- The typhus epidemic -- The Althoff massacres -- Tartak -- pt. 4. Stabilization -- The Kolditz era : summer-fall 1943 -- Jewish work -- Food, property, and the underground economy -- The Ukrainian guards -- Poles and Jews -- Children in the camps -- Childbirth, abortion, sex, and rape -- The Schroth era : winter-spring 1944 -- pt. 5. Consolidation, escape, evacuation -- Closing Majówka and Tartak -- The final days -- From Starachowice to Birkenau -- The Starachowice women and children in Birkenau -- Escapees -- pt. 6. Aftermath -- Return to and flight from Wierzbnik -- Postwar investigations and trials in Germany -- Conclusion